Analyzing Pronoun Usage in Yelp Reviews - McMahon, Nicole; Dekan, Garrett; Amthauer, Heather (My University, 2019)
The pronouns an individual chooses when speaking or writing can reveal a considerable amount about him or her. This research project examines whether the emotional aspect of an experience has any influence on the types of pronouns that a person uses. We accomplish this task by analyzing Yelp reviews and determining whether the pronouns a person chooses when writing a review correspond to the rating, he or she gives that experience on a scale of one to five stars. This research is significant because any correlation we find would indicate that people use different types of pronouns when describing positive experiences as opposed to negative experiences. Our conclusions could be used to infer the emotional state of the author of any informal piece of writing, which would help readers determine if the author has any underlying bias toward the subject.
Color poster with text, charts, and graphs.
Keywords: Pronouns; Emotions; Internet marketing; Posters